2012
DOI: 10.1097/id.0b013e31826a583d
|View full text |Cite
|
Sign up to set email alerts
|

The Success Rate of Narrow Body Implants Used for Supporting Immediate Provisional Restorations

Abstract: With a favorable implant survival rate, the use of NBIs to support provisional restorations seemed to be a feasible treatment option. In addition, there is merit for research on the long-term use of NBIs-supported final prostheses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
4
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 19 publications
1
4
0
Order By: Relevance
“…This would indicate the absence of excessive mechanical loading on the 2.5‐mm–diameter implants. Similar results have been reported by Arisan and colleagues and Wang and colleagues …”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This would indicate the absence of excessive mechanical loading on the 2.5‐mm–diameter implants. Similar results have been reported by Arisan and colleagues and Wang and colleagues …”
Section: Discussionsupporting
confidence: 92%
“…Similar results have been reported by Arisan and colleagues and Wang and colleagues. 9,32 This study suffers from the limitation of a retrospective study design and the small sample size. The retrospective study provides evidence of lesser strength than the evidence derived from prospective or randomized clinical trial.…”
Section: Discussionmentioning
confidence: 99%
“…As a result of this confusion, it is not unexpected to find in the literature an implant with known diameter (1.8 mm) that has four different classifications in four different studies (mini, 12 small, 4 narrow, 13 and very small 14 ). Another example of unconformity would be when two different terms were used 3 Ioannidis et al 2015, 9 Lee et al 2013, 13 Froum et al 2007, 33 Degidi et al 2008, 34 Veltri et al 2008, 35 Franco et al 2009, 36 Anitua et al 2010, 37 Arisan et al 2010, 38 Malo & de Araujo Nobre 2011, 39 Sohn et al 2011, 40 Galindo-Moreno et al 2012, 41 Mazor et al 2012, 42 Mohamed et al 2012, 43 Sallam et al 2012, 44 Wang et al 2012, 45 Benic et al 2013, 46 Zweers et al 2013 47 Small 9 4,6,7,15,16,[48][49][50][51] Jackson 2011, 4 Christensen 2009, 6 Al-Nawas et al 2012, 7 Flanagan 2006, 15 Flanagan 2008a, 16 Vigolo et al 2004, 48 Yaltirik et al 2011, 49 Polack & Arzadon 2012, 50 Sohrabi et al 2012 51 Very Small 2 14,16 Flanagan et al 2008, 14 Flanagan 2008a 16 Mini 6 5,14,16,[5...…”
mentioning
confidence: 99%
“…This could be of interest when comparing the results of this study with those of other researchers. Limited bucco-lingual bone crest width has always been one of the main indications for placement of narrow implants (17)(18)(19)(20)(21)(22)(23). The BL of narrow implants without bone regeneration was compared with the BL of conventional implants that used bone regeneration to gain bucco-lingual crest width.…”
Section: Discussionmentioning
confidence: 99%
“…The present study found no incidence of fracture in the implants studied. Wang et al (19) determined a survival rate of 93.5% based on 31 narrow implants observed over one year. On the other hand, Anitua et al (2) placed 89 narrow implants, using prostheses similar to those in the present study (overdentures, single crowns and implants splinted) and evaluating the implants after 4 years.…”
Section: Discussionmentioning
confidence: 99%